Der Brückenbauer. Intervista con Dario Siddi - Usadel, Marie; Corgiolu, Francesco (Ex Novo: Journal of Archaeology, 2021)
Dario Siddi was a teacher and a student, theater director and actor, an archaeologist. Born in 1944 he lived and worked as a middle school teacher in Sant’Antioco and Calasetta in Sardinia. In 1988 he founded Il Calderone, a small theater company: however, over time the association would also become active in other areas of social and cultural life in Sant’Antioco, from the integration of immigrants to the organization of cinematic events. After his passing in 2020 his friends called him a bridge-builder, which is probably the best description of the role he played in the archaeological life of Sant’Antioco. Together with his fellow members of Il Calderone he initiated a cooperation with researchers of the Ruhr-University Bochum (Germany). The resulting archaeological project, under the direction of Constance von Rüden, is aimed at investigating the prehistoric settlement system of the Canai-plain in the southern part of Sant’Antioco with a particular interest in the Nuragic period. Since 2017 there have been annual field campaigns comprising a systematic survey in the plain, targeted prospection of the surrounding Nuragic sites as well as the detailed documentation of the area called Gruttiacqua in the south-western part of the Canai-plain. In 2019 it was possible to begin excavating part of the Nuragic village of Gruttiacqua. Since this project represents one of the rare cases where the archaeologists were chosen by the community and not the other way around, the cooperation between students, international researchers and members of Il Calderone is an essential, original element that directly and more effectively involves the local community.